THE EFFECT OF ENTERPRISE RISK MANAGEMENT AND INVESTMENT DECISION ON FIRM VALUE DURING THE COVID-19 PANDEMIC (EVIDENCE FROM HOTELS, RESTAURANTS, AND TOURISM COMPANIES LISTED IN INDONESIA STOCK EXCHANGE 2020-2021) - Ummu Hanifah; Maria Th. Heni Widyarti; Sri Hardiningsih (Applied Accounting and Management Review (AAMAR), 2022)
This study aims to analyze the effect of Enterprise Risk Management (ERM) and investment decision with firm size, leverage, and managerial ownership as control variables on firm value during the Covid-19 pandemic, either simultaneously or partially. The population of this study is hotel, restaurant, and tourism companies listed in Indonesia Stock Exchange 2020-2021. The sample was selected using purposive sampling method with a total sample of 26 companies. The method of analysis in this study using multiple linear regression. The results showed thatEnterprise Risk Management (ERM) and investment decision with firm size, leverage, and managerial ownershipsimultanously had a significant effect on firm value as indicated by the value of Fcount>Ftable, which was 5.553 > 2.42 with a significance level of 0.000 from significance level of 0.05. The partial test shows that Enterprise Risk Management (ERM), investment decision, and managerial ownership have no significant effect on firm value. Partially, firm size has a significant negative effect on firm value. And leverage partially has a significant positive effect on firm value.